Development and evaluation of an intervention to promote the use of eyeglasses among Romani families in Bulgaria - Kodjebacheva, Gergana Damianova; Hristova, Slavka Grigorova; Savov, Ventsislav (Frontiers in Public Health, 2023)
Objective Uncorrected refractive error (i.e., lack of eyeglasses for the treatment of refractive error) is one of the leading causes of visual impairment in Eastern Europe. Limited information is available on how to promote the use of eyeglasses among Romani families in Bulgaria. In step 1, the objective was to obtain suggestions by Romani mothers on how to promote the use of eyeglasses among children. In step 2, the objective was to evaluate an intervention to promote the use of eyeglasses based on suggestions received during step 1. Methods During step 1, 5 focus groups with Romani mothers took place in one neighborhood in Bulgaria. During step 2, the intervention used a one-group pre-test, post-test design. Families received eye examinations. Those who needed eyeglasses chose attractive eyeglasses. Parents received education on how to encourage their children to wear eyeglasses. Results During step 1, 54 mothers participated. Mothers suggested that the whole family should receive eye examinations and eyeglasses. During step 2, of 33 family members, 14 did not have refractive errors and 19 did. Of the 19 family members with refractive error, none had eyeglasses at pre-test. Approximately 6 months following the end of the intervention, 11 of the 19 family members (57.9%) wore eyeglasses and the remaining 8 (42.1%) did not. Conclusion Romani family members needed eyeglasses but did not have any at pre-test of the intervention. Future interventions that offer education on the importance of eye examinations may increase receipt of eye examinations and adherence to wearing eyeglasses.